Pharmacy and Pharmacist; Interchangeably Misunderstood Role - Nugroho, Agung (ScieClouds Publishing, 2023)
This article discusses the outline of a pharmacy and pharmacist. In this article, it is explained how the role of the pharmacy and pharmacist as the person in charge of a pharmacy has a big role. The purpose of implementing this article is to increase the understanding of prospective pharmacists about the roles, functions, positions and responsibilities of pharmacists in pharmacy services in pharmacies, to equip prospective pharmacists to have insight, knowledge, skills, and practical experience to do pharmacy work in a pharmacy, providing opportunities for prospective pharmacists to see and study strategies and activities that can be carried out in the context of developing community pharmacy practices in pharmacies, preparing prospective pharmacists to enter the world of work as professional pharmaceutical personnel and providing a real picture of the problems of pharmaceutical work in pharmacies